Defining the Roles of the Cation Diffusion Facilitators in Fe2+/Zn2+ Homeostasis and Establishment of Their Participation in Virulence in Pseudomonas aeruginosa - Salusso, Agostina; Raimunda, Daniel (Frontiers in Cellular and Infection Microbiology, 2017)
Transporters of the cation diffusion facilitator (CDF) family form dimers that export transition metals from the cytosol. The opportunistic pathogen Pseudomonas aeruginosa encodes three homologous CDF genes, czcD (PA0397), aitP (PA1297), and yiiP (PA3963). The three proteins are required for virulence in a plant host model. Disruption of the aitP gene leads to higher Fe2+ and Co2+ sensitivity together with an intracellular accumulation of these ions and to a decreased survival in presence of H2O2. Strains lacking czcD and yiiP showed low Zn2+ sensitivity. However, in iron-rich media and in the presence of Zn2+ these strains secreted higher levels of the iron chelator pyoverdine. Disruption of czcD and yiiP in a non-pyoverdine producer strain and lacking the Zn2+-transporting ATPase, increased the Zn2+ sensitivity and the accumulation of this ion. Most importantly, independent of the pyoverdine production strains lacking CzcD or YiiP, presented lower resistance to imipenem, ciprofloxacin, chloramphenicol, and gentamicin. These observations correlated with a lower survival rate upon EDTA-lysozyme treatment and overexpression of OprN and OprD porins. We hypothesize that while AitP is an Fe2+/Co2+ efflux transporter required for Fe2+ homeostasis, and ultimately redox stress handling, CzcD, and YiiP export Zn2+ to the periplasm for proper Zn2+-dependent signaling regulating outer membrane stability and therefore antibiotic tolerance.